Poly(dl‐Lactic Acid)‐Based Linear Polyurethanes Capable of Forming Physical Crosslinking via UPy Quadruple Hydrogen Bonding Assembly. Issue 7 (9th June 2020) - Chen, Yimei; Meng, Yanli; Luo, Yanfeng; Wang, Yuanliang
Abstract: Linear shape memory polyurethanes based on poly(dl ‐lactic acid) (PDLLA) macrodiol (PDLLA‐SMPUs) have various advantages such as good processability, biodegradability, shape memory effect, and biocompatibility, yet the insufficient mechanical properties prevent their effective applications in bone repair. 2‐Ureido‐4[1 H ]‐pyrimidone (UPy) can form strong quadruple hydrogen bonding. Here, a new linear PDLLA‐SMPU containing pendant UPy units (UPy‐ p ‐PDLLA‐SMPU) is designed and synthesized. The pendant UPy units may dimerize to form physical crosslinking among UPy‐ p ‐PDLLA‐SMPU chains. As a result, UPy‐ p ‐PDLLA‐SMPU demonstrates both good processability and significantly higher mechanical properties than the corresponding linear PDLLA‐SMPU without pendant UPys. In addition, UPy‐ p ‐PDLLA‐SMPU shows excellent shape memory effect near body temperature, with a shape fixity ratio of up to 98.6% and a recovery ratio of up to 92.9%. This work provides a new strategy to design SMPUs integrating the merits of linear and crosslinked polyurethanes, and the obtained UPy‐ p ‐PDLLA‐SMPU is a promising material for bone tissue repair in view of the mechanical, thermal, and shape memory properties. Abstract : A new linear poly(dl ‐lactic acid)‐based polyurethane containing pendant 2‐ureido‐4[1 H ]‐pyrimidone (UPy) units is designed so as to possess physically crosslinked network due to the strong quadruple hydrogen bonding between UPy units and the reversible formation of hydrogen bonds. It integrates the advantages of both linear and crosslinked polyurethanes, including good processability, high mechanical properties, and excellent shape memory performance.